Postelimination Cluster of Lymphatic Filariasis, Futuna, 2024 - Clément Couteaux; Thibaut Demaneuf; Laurent Bien; Manuel Munoz; Bernadette Worms; Samuel Chésimar; Gwenael Takala; Atonio Lie; Vincent Jessop; Malia Kalemeli Selemago; Valelia Uhila; Monika Toa; et al. (Emerging Infectious Diseases)
After detection of 2 clinical lymphatic filariasis (LF) cases in a postelimination context in 2023 on the island of Futuna (Wallis and Futuna archipelago), the Wallis and Futuna Health Agency conducted a LF prevalence survey in Futuna in May 2024. This cross-sectional study, carried out among schoolchildren <18 years of age, identified 5 children with antigenemia, indicating an estimated antigenemia prevalence in Futuna children nearing 2%. The study also confirmed a spatial cluster of cases in the village of Taoa, where the child antigenemia prevalence reached 7.5% (95% CI 2.1%–18.2%), and demonstrated a link between infection and traditional housing. We observed microfilariae in contact cases during secondary investigations. These findings suggest resurgence of LF in a postelimination context, in which the expected child antigenemia prevalence should not exceed 1%. This situation should prompt a new mass drug administration campaign using triple therapy and the reinforcement of epidemiologic and entomologic surveillance.